2009
DOI: 10.1890/07-1550.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of insect herbivory on cactus population dynamics: experimental demography across an environmental gradient

Abstract: Miller, Tom E. X.; Louda, Svata M.; Rose, Karen A.; and Eckberg, James O., "Impacts of insect herbivory on cactus population dynamics: experimental demography across an environmental gradient" (2009 Abstract. Understanding the role of consumers in plant population dynamics is important, both conceptually and practically. Yet, while the negative effects of herbivory on plant performance have been well documented, we know much less about how individuallevel damage translates to impacts on population growth or wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 84 publications
(134 reference statements)
3
110
3
1
Order By: Relevance
“…Our work was conducted at the Sevilleta National Wildlife Refuge, a long-term ecological research (LTER) site in Socorro County, New Mexico, USA. See Miller et al (2009) for a description of the study area.…”
Section: Study Site and Focal Organismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work was conducted at the Sevilleta National Wildlife Refuge, a long-term ecological research (LTER) site in Socorro County, New Mexico, USA. See Miller et al (2009) for a description of the study area.…”
Section: Study Site and Focal Organismsmentioning
confidence: 99%
“…), and a noctuid moth (Cahela ponderosella). Insect exclusion experiments demonstrated that these herbivores depress plant population growth (Miller et al 2009). …”
Section: Study Site and Focal Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments that manipulate herbivory across a wide gradient of arriving propagules during the initial The relative importance of propagule pressure and herbivory by native consumers is likely to vary across heterogeneous landscapes. This can result from spatial variation in generalist and specialist herbivore density or feeding activity (Louda and Rodman 1996, Lambrinos 2002, Miller et al 2009), or from the interaction of herbivory with spatial heterogeneity in abiotic conditions and plant community composition (Lambrinos 2002). To date, our knowledge of propagule pressure and ecosystem factors influencing invasions across the landscape is based primarily on observational studies that substitute indirect (ship traffic) or nonindependent (distance to propagule source) measures for propagule pressure (Eschtruth andBattles 2009, Simberloff 2009).…”
Section: Introductionmentioning
confidence: 99%